PEMBINAAN REMAJA PUTRI DALAM ADAB BERPAKAIAN SESUAI SYARIAT ISLAM - Rusiadi Rusiadi (Cross-border, 2020)
Coaching is an action, process, result or statement to be even better. In this case, it shows the ability to increase growth, or increase something to encourage people to practice faith and piety in everyday life. Coaching is basically related to functions and efforts to improve human usability in a collaborative process to achieve a goal, in this case it is carried out through efforts to create an atmosphere or work climate that encourages optimal development of potential. A teenager in dressing certainly really needs guidance from parents, especially for young women, where adolescence is very challenging, one of which is in the manners of dress, a lot of teenagers are influenced by the environment and from the internet about dressing that is not in accordance with Islamic law The severity of these challenges makes parents have to have thorough preparation in nurturing their children, especially young women so as to produce teenagers who are resilient to changing times and still adhere to Islamic law.